Implementasi Konsep Ta’dib menurut Adian Husaini sebagai Solusi Terhadap Problematika Senioritas dan Kekerasan di Pesantren - Zahwa, Afaf Mulia; Alifah, Aulia Nurul; Adha, Hanifatul (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
This study examines the issue of deviant seniority practices and violence in Islamic boarding schools (pesantren), which contradict the school's function as an institution for moral and character education. This phenomenon demonstrates a gap between the normative values of Islamic education and social practices in Islamic boarding schools. This study aims to analyze the concept of ta'dib (religious guidance) as a conceptual framework for responding to and addressing deviant seniority practices and violence in Islamic boarding schools. The study employed a qualitative method with a literature review approach, through a critical analysis of scientific works, academic journals, and the thoughts of Ustadz Dr. Adian Husaini on the concept of ta'dib in Islamic education. The data were analyzed using thematic analysis techniques to identify ta'dib principles relevant to the formation of civilized social relations in Islamic boarding schools.The results indicate that the concept of ta'dib, which emphasizes the integration of mastery of knowledge ('ilm), the teaching process (ta'lim), and moral-spiritual development (tarbiyah), has strong relevance as a preventive and corrective approach to deviant seniority practices.